Obesity, diabetes, serum glucose, and risk of primary liver cancer by birth cohort, race/ethnicity, and sex: Multiphasic health checkup study. (June 2016) - Petrick, Jessica L.; Freedman, Neal D.; Demuth, Jane; Yang, Baiyu; Van Den Eeden, Stephen K.; Engel, Lawrence S.; McGlynn, Katherine A.
Abstract: Objective: Obesity and diabetes have been associated with liver cancer. However, recent US-based studies have suggested a lack of association between obesity and liver cancer among blacks and women. Methods: We conducted a nested case-control study within the Multiphasic Health Checkup (MHC) cohort of Kaiser Permanente Northern California (KPNC) members. Liver cancer was diagnosed using the KPNC Cancer Registry. Detailed self-administered questionnaires and a standardized examination that included measurement of height and weight and a 1-h glucose tolerance test were completed prior to diagnosis of liver cancer for cases (n = 450) and matched controls (4489). Height and weight were utilized to calculate BMI (kg/m 2 ) as a measure of adiposity: underweight (15⿿⿤8.5 kg/m 2 ), normal weight (18.5⿿⿤25 kg/m 2 ), overweight (25⿿⿤30 kg/m 2 ), and obese (⿥30 kg/m 2 ). Conditional logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CI) for the association between BMI, diabetes, and serum glucose with subsequent incidence of liver cancer, in models that were stratified by birth cohort, race/ethnicity, and sex. Results: Compared to normal weight individuals, obese individuals had a 2.4-fold increased risk of liver cancer (OR = 2.38, 95% CI: 1.68⿿3.36), and overweight individuals had a 32% increased risk (OR = 1.32, 95% CI: 1.03⿿1.70). This association did not differ when stratified by birth cohort, race/ethnicity, or sex (pint > 0.05). Among blacks and women, obesity was associated with at least a 2-fold increased risk of liver cancer (OR = 2.29, 95% CI: 1.22⿿4.28 and OR = 2.00, 95% CI: 1.14⿿3.52, respectively). More moderate increased odds ratios were noted for diabetes (OR = 1.28, 95% CI: 0.65⿿2.54) and serum glucose ⿥200 mg/dL (OR = 1.63, 95% CI: 0.48⿿5.55), although the results did not attain statistical significance. Conclusion: In summary, our finding of a positive association between obesity and liver cancer suggests that a higher BMI may increase the risk of liver cancer in the US, for both sexes and all race/ethnicities.